Educational Discrimination and Access to Schooling An Investigative Study of the Santal Girls - Das, Pankaj (JOURNAL OF INDIAN EDUCATION, 2022)
Right to Education Act, 2009 ensures educational opportunity to all children however, after so many years since the passing of such an act, we find that the tribal children especially, the Santal girls in the specific region of Odisha are still facing educational discrimination and are denied their fundamental rights to access to education. Against this backdrop, this paper is an attempt to investigate the magnitude and the extent of educational discrimination of Santali girls of Mayurbhanj district in the state of Odisha. The findings of the study reflect the fact that there is a wide gap in the gender parity index. Further the lack of adequate infrastructure, non-conducive learning environment, deplorable socio-economic conditions of the tribal communities, apathy of teachers also causing the dilapidated of girls’ education in tribal areas. The tribal girls are excluded from elementary education due to their socio-cultural disparities and barriers. Therefore, policy imperatives call for total revamp of tribal education. However, mere policy inputs will not address real educational problems of tribal girls until much emphasis put on the delivery mechanisms of these policy inputs at the grounds level. So, any policy formulations for enhancing the education of tribal girls in the tribal belt must be insisted on ‘process-oriented’ rather than ‘purpose-oriented’.